Ensuring Social Security for All: Key Considerations for Policy Options in Indonesia - Iene Muliati; Utomo Sarjono Putro; Yudo Anggoro (Policy & Governance Review, 2021)
Social security is an essential instrument for protecting people from falling into poverty due to economic shocks in the event of sickness, work-accident, old age, and death of income producers. Indonesia introduced Law no. 40 Year 2004 on National Social Security System to implement mandatory social security programs for all. Despite the compulsory participation for all, the national social security system's coverage continues to be low and mostly relies on government aids. This study explores and analyzes key factors that need to be considered during the policy options formulation process to ensure the intended policy can support the national social security system's implementation. The findings show the need to build an integrated ecosystem model that is critical for social security implementation by considering the combined use of decision-making approaches and five consideration factors during the policy options formulation. An integrated ecosystem model contributes better policy options formulation that can support the effective implementation of the national social security programs while minimizing implementation risks.